Economic Contribution to Local Livelihoods and Households Dependency on Dry Land Forest Products in Hammer District, Southeastern Ethiopia - Dagm Fikir; Wubalem Tadesse; Abdella Gure (International Journal of Forestry Research)
The study was conducted in Hammer district, Southern Ethiopia, to provide empirical evidence on economic contribution to local livelihoods and households dependency on dry forest products. One agropastoral and two pastoral kebeles were purposively selected, and data was collected through household survey, group discussions, market assessments, and field observation. A total of 164 households, selected based on a random sampling procedure, were interviewed using structured questionnaire. The study found that income from forest products contributes 21.4% of the total annual household income. The major dry forest products include honey, fuel wood, gum and resin, and crafts and construction materials, contributing 49%, 39%, 6%, and 6% of the forest income, respectively. Households of the pastoral site earned more forest income and were relatively more dependent on forest products income than those in the agropastoral study site. Significant variation was also found among income groups: households with higher total annual income obtain more forest income than those with lower income, but they are relatively less dependent on forest products than the lower counterpart. Besides, various socioeconomic and contextual factors were found to influence forest income and dependency. The findings of the study provide valuable information up on which important implications for dry land forest development and management strategies can be drawn.